Helicon full-wave modeling with scrape-off-layer turbulence on the DIII-D tokamak. (25th November 2021) - Lau, Cornwall; Brookman, Michael; Dimits, Andris; Dudson, Ben; Martin, Elijah; Pinsker, Robert I.; Thomas, Matt; Van Compernolle, Bart
Abstract: Helicon waves have been recently proposed as an off-axis current drive actuator due to their expected high current drive efficiency in the mid-radius region in high beta tokamaks. This paper focuses on a numerical study to better understand effects of scrape-off-layer (SOL) turbulence on helicon wave propagation and absorption on the DIII-D tokamak using a recently developed helicon full-wave model with turbulent density inputs from synthetic single wavelength SOL turbulence and first-principles HERMES multi-wavelength turbulence models. With both input turbulence models, three key effects are observed: the helicon wave can scatter to undesirable locations in the plasma, large helicon wave electric fields can form in localized regions near the SOL turbulence, and the helicon wave can mode convert to slow waves in the SOL. This is shown to cause helicon wave refraction to undesirable locations and strong helicon wave absorption in the SOL resulting in significantly less helicon wave power in the core plasma. Using synthetic SOL turbulence, the simulations additionally show that high amplitudes and long wavelengths greater than a few cm on average have the largest effect on modifying the helicon wave propagation and absorption; the modeling predicts, for example, that approximately 60% of helicon power can be absorbed in the SOL for ñ / n ∼ 0.8 and lambda_perp ∼ 0.05 m. Several potential physical mechanisms that may explain the interaction of helicon waves with SOL turbulence in these simulations are discussed.